The Firebombing of Tokyo: Views from the Ground - Cary Karacas; Bret Fisk (Asia-Pacific Journal, 2011)
More than sixty-five years after the Great Tokyo Air Raid of March 10, 1945, and the subsequent firebombing and destruction of Japan's cities by the United States Army Air Forces in World War II, the issues remain little known and less studied. In stark contrast to the atomic bombing of Hiroshima and Nagasaki, however, historians and other scholars working in the English language have paid little attention to the tremendous societal impact - both immediate and long-lasting - of the destruction by firebombing of Japan's cities. What remain particularly underdeveloped are an historical understanding and appreciation of the Japanese civilian experience, specifically an understanding of the effect of the air raids on Japanese communities, cities, and social institutions. This special issue locates the firebombing of Tokyo and Japanese cities within the framework of the growing literature on the bombing of cities and civilians in twentieth century warfare. Bret Fisk and Cary Karacas introduce the issues and their important new website and teaching resource on the air raids: japanairraids.org.